Polymer-based flexible NOx sensors with ppb-level detection at room temperature using breath-figure molding. Issue 38 (23rd September 2019) - Yu, Seong Hoon; Girma, Henok Getachew; Sim, Kyu Min; Yoon, Seongwon; Park, Jong Mok; Kong, Hoyoul; Chung, Dae Sung
Abstract : A direct/facile strategy for synchronizing the gas receptor and signal transport layers is demonstrated for highly sensitive flexible NO x sensors. Abstract : A strategically designed polymer semiconductor thin film morphology with both high responsivity to the specific gas analyte and high signal transport efficiency is reported to realize high-performance flexible NO x gas sensors. Breath-figure (BF) molding of polymer semiconductors enables a finely defined degree of nano-porosity in polymer films with high reproducibility while maintaining high charge carrier mobility characteristics of organic field effect transistors (OFETs). The optimized BF-OFET with a donor–acceptor copolymer exhibits a maximum responsivity of over 10 4 %, sensitivity of 774% ppm −1, and limit of detection (LOD) of 110 ppb against NO at room temperature. When tested across at NO concentrations of 0.2–10 ppm, the BF-OFET gas sensor exhibits a response time of 100–300 s, which is suitable for safety purposes in practical applications. Furthermore, BF-OFETs show a high reproducibility as confirmed by statistical analysis on 64 independently fabricated devices. The selectivity of NO x analytes is tested by comparing the sensing ability of BF-OFETs with those of other reducing gases and volatile organic compounds; the BF-OFET gas sensor platform monitors specific gas analytes based on their polarity and magnitude of sensitivity. Finally, flexible BF-OFETs conjugated with plastic substrates are demonstrated and they exhibit a sensitivity of 500% ppm −1 and a LOD of 215 ppb, with a responsivity degradation of only 14.2% after 10 000 bending cycles at 1% strain.